Metabolic balancing by miR-276 shapes the mosquito reproductive cycle and Plasmodium falciparum development - Lena Lampe (Nature Portfolio, 2019)
Plasmodium growth is adapted to the reproductive cycle of mosquitoes, but underlying mechanisms are unclear. Here, Lampe et al. show that the blood-meal induced miR-276 balances the termination of the mosquito amino acid catabolism and egg development, providing nutrients for Plasmodium sporozoite development.